RECOGNIZING THE RIGHT OF THE THIRD GENDER TO MARRIAGE AND INHERITANCE UNDER HINDU PERSONAL LAW IN INDIA - D. Chowdhury; A. Tripathy (BRICS Law Journal, 2016)
One of the most implicit foundations of a person’s identity today, in a cultural, national as well as global context, is the collegial relationship which he or she shares with another person, that relationship ultimately giving formation to a conjoint, consolidated and co-dependent recognition of the two as one under the law, particularly with respect to resolving socio-familial issues such as those of parentship, guardianship, adoption, succession and inheritance, among others.The term “relationship” mentioned above is connotative of marriage and the following paper attempts to look at this relationship, in its connection to the various facets of one’s personal identity as a citizen, from the perspective of a third gender Hindu Indian national. Though the right to marry of such an individual, especially as seen against the backdrop of the existing communal ethos in the country, may be accepted as being some form of a heterodoxy, it still falls short of qualifying as anything that could be called, in the least, “heretical” or even illegal.While due to the constraints of time the authors of the present study have been compelled to restrict the same to only a particular division of nationality and a further specific sub-class thereof, the authors sincerely hope that this study will inspire further such examinations into its chosen subject within the field domains of other religions and nationalities.